Absorption of THz electromagnetic wave in two mono-layers of graphene. (14th April 2016) - Reynolds, Cole B; Shoufie Ukhtary, M; Saito, Riichiro
Abstract: Nearly 100% absorption of an electromagnetic (EM) wave in terahertz (THz) frequency is proposed for a system consisting of two mono-layers of graphene. Here, we demonstrate that the system can almost perfectly absorb an EM wave with frequency of 2 THz, even though we have a low electron mobility of roughly 1000 cm 2 Vs −1 . The absorption probability is calculated by using the transfer matrix method. We show that the two mono-layers of the graphene system is needed to obtain nearly 100% absorption when the graphene has a relatively low Fermi energy. The absorption dependence on the distance between the graphene layers is also discussed.